Stand-up Comedy as a Genre of Intimacy - Brodie, Ian (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
Through their use of amplification, stand-up comedians are able to engage an audience at a natural register, employing the modes of everyday, interpersonal, conversational speech, avoiding for the most part the distancing required for most forms of cultural performance. By maintaining control of this conversation, they are able paradoxically to give control away, wresting it back when required, thus creating the illusion of intimacy, exchange, and reciprocity between themselves and the audience. This article provides the beginnings of a framework for understanding stand-up comedy and its relationship to folkloric genres by placing intimacy, not humour, as the primary consideration.